Syncytins expressed in human placental trophoblast. (15th September 2021) - Roberts, R. Michael; Ezashi, Toshihiko; Schulz, Laura C.; Sugimoto, Jun; Schust, Danny J.; Khan, Teka; Zhou, Jie
Abstract: Three versions of syncytiotrophoblast exist in the human placenta: an invasive type associated with the implanting conceptus, non-invasive villous type of definitive placenta, and placental bed giant cells. Syncytins are encoded by modified env genes of endogenous retroviruses (ERV), but how they contribute functionally to placental syncytial structures is unclear. A minimum of eight genes ( ERVW1, ERVFRD-1, ERVV-1, ERVV-2, ERVH48-1, ERVMER34-1, ERV3-1, & ERVK13-1 ) encoding syncytin family members are expressed in human trophoblast, the majority from implantation to term. ERVW1 (Syncytin 1) and ERVFRD-1 (Syncytin 2) are considered the major fusogens, but, when the expression of their genes is analyzed by single cell RNAseq in first trimester placenta, their transcripts are distinctly patterned and also differ from those of their proposed binding partners, SLC1A5 and MFSD2A, respectively. ERVRH48-1 (suppressyn or SUPYN) and ERVMER34-1 are probable negative regulators of fusion and co-expressed, primarily in cytotrophoblast. The remaining genes and their products have been little studied. Syncytin expression is a feature of placental development in almost all eutherian mammals studied, in at least one marsupial, and in viviparous lizards, which lack the trophoblast lineage. Their expression has been inferred to be essential for pregnancy success in the mouse. All the main human ERV genes arose following independent retroviral insertion events, none of which trace back to the divergence of eutherians and metatherians (marsupials). While syncytins may be crucial for placental development, it seems unlikely that they helped orchestrate the divergence of eutherians and marsupials. Highlights: Eight syncytin genes are expressed in human trophoblast from implantation to term. Expression of the main ERV genes in placenta is differentially patterned. Patterning of ERVW1 and ERVFRD-1 and their proposed binding partners differs. Placental ERV gene expression is not unique to eutherian mammals.